Images of the 'other': the visual representation of African people as an indicator of socio-cultural values in nineteenth century England - Buntman, Barbara (My University, 1994)
This research examines the way in which the ideology of difference is reflected in visual images of black people in Britain in the nineteenth century, Concepts of tlie 'other' ar~iocated within specific contemporary socie-celnnal and political contexts. Historically, this was an important period in which theories of human difference proliferated, and which in turn informed diverse and often contradictory social practices. The white English behavioUl' towards, and perspective of, black people in England had a direct bearing not only on life in Britain, but in the colonies as well. The images produced in England were critical to the colonial enterprise. They infomlt:al Briti~h attitudes to Africa and the Empire more generally. Implicit in the analysis of the images is an evaluation of the emergflllce of hegemonic ideas, and the manipulation of power by the ruling class. The beliefs and trends of a society are reflected in its visual arts. The methodology employed aims to bring together analyses of the production of visual representations within a broad chronological and thematic framework, so as to assess the social production of meaning in the images. To do this it is necessary to verify the presence of black people as residents in England. Chapter one addresses this issue as well as determines to what extent the notion of blackness was integral to an early formation of a black !~~creotype. Some of the implications of British participation in the slave trade are also censldered, Images of slaves which are the main focus of chapter two, demonstrate seclo-eultural attitudes of early nlneteanth-centurv English people. Chapter three examines the rise of science and systematic knowlaJge which fed to both technical and popular theorising about racial difference. The congruence between scientific and popular understandings led to the emergence of notions of 'types' and hierarchies of people, which were to dominate ideas and attitudes for decades. Concurrent with the rise of science was the growth of a popular image of a stereotyped blar.k 'other', Chapter four evaluates the. processes through which these images were disseminated in a fast growing popular culture. The inequalities ()f power relations within English society, as manifest in the images, are analyzed. Chapter five considers the ways in which the white male producers of images perceived black women. The contradictions and ambiguities of the visual systems in this chapter point to the complexities of cultural practice, and of artists and producers' particular views on blackness and femaleness. The conclusion summarises the lIIIay in which the coneept of an 'other' has been used in this dissertation.
Dissertation submitted in fulfilment of the requirements for the Degree of Master of Arts at the University of the Witwatersrand. March 1994.
Keywords: Racism--England--19th century; Blacks--England--Public opinion--19th century; Blacks in art; England--Race relations--19th century